A comparison of destinations’ impacts on hotel rates - Soler-García, Ismael Pablo; Gemar-Castillo, Germán; Guzmán-Parra, Vanesa Francisca (Elsevier, 2019)
The impact of destinations’ attributes on hotel rates in different locations has been insufficiently compared the existing literature. This study sought to apply the hedonic pricing method to measure and compare how room prices are affected by factors that are both external and inherent to hotel companies. After collecting nearly all the data regarding hotel features that consumers can use to make choices about accommodations on the TripAdvisor website, different models were developed for each city and season. The results suggest that hotels in Barcelona are more dependent on external conditions than hotels in Madrid are. In addition, hotels in both cities are more affected by external conditions during the high season. This paper discusses these and other results, as well as their implications.
Keywords: Hoteles y pensiones - Precios; Barcelona; Destination; External dependency; Hedonic price model; Madrid; TripAdvisor